Incidence and risk of respiratory tract infection associated with specific drug therapy in pulmonary arterial hypertension: a systematic review. Issue 1 (December 2017) - Gu, Zhichun; Zhang, Chi; Wei, Anhua; Cui, Min; Pu, Jun; Lin, Houwen; Liu, Xiaoyan
Abstract Specific drug therapy has been proven to improve functional capacity and slow disease progression in pulmonary arterial hypertension (PAH), regretfully with the data on the risk of respiratory tract infection (RTI) associated with specific drug therapy being limited. Databases of Medline, Embase, Cochrane Library and the ClinicalTrials.gov Website were searched for randomized controlled trials (RCTs) that reported the RTI data of PAH-specific drug therapy in patients. The primacy outcome was assessed by employing a fixed-effects model. Totally, 24 trials involving 6307 patients were included in the analysis. PAH-specific drug therapy was not significantly associated with the increased risk of both RTI (19.4% vs. 21.1% RR 1.02, 95%CI 0.92–1.14, P = 0.69) and serious RTI (4.3% vs. 5.0% RR 0.99, 95%CI 0.77–1.26, P = 0.93) compared to placebo. The results were consistent across the key subgroups. No heterogeneity between the studies (I2 = 35.8% for RTI, and I2 = 0.0% for serious RTI) and no publication bias was identified. In conclusion, no significant increase in RTI had been found in PAH-specific drug therapy when compared with placebo. Whereas, RTI in PAH patients is still worthy of clinical attention.